Exploring the Challenges of Implementing Guidelines for the Design of Visual Analytics Systems. (September 2015) - Haider, Johanna; Pohl, Margit; Hillemann, Eva-Catherine; Nussbaumer, Alexander; Attfield, Simon; Passmore, Peter; Wong, B. L. William
Intelligence analysis activities are increasingly seen as a sense-making activity. Information systems supporting these activities have, therefore, to be designed in a way to enable analysts to engage in sensemaking in an efficient manner. In the context of the VALCRI project, we developed guidelines for an appropriate design of intelligence analysis systems. Such guidelines can be very valuable in the design process, but their application is sometimes not straightforward. We describe such problems and also suggest possible solutions for these application problems within the context of intelligence analysis.